The Novice Mathematics Teachers' Technological Pedagogical Content Knowledge: A Case Study - Pagiling, Sadrack Luden; Nur'aini, Khumaeroh Dwi; Mokoagow, Eka Indrysari (SEAMEO Regional Centre for QITEP in Mathematics, 2023)
This study seeks to characterize the Technological Pedagogical Content Knowledge of novice lower secondary mathematics teachers who do and do not possess an educator certificate based on the components of Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical Content Knowledge (TPACK). This research employed a case study approach conducted in two secondary schools in Merauke Regency. Two secondary mathematics teachers with a bachelor's degree in mathematics education and five years of teaching experience were recruited as participants. We collected data from learning classroom observation guidelines, learning-practice interviews, and task-based interviews. Findings show that certified teachers can implement learning according to the lesson plans that have been designed and can teach and answer questions about the assigned material effectively. Meanwhile, the uncertified teacher performs excellently using technology, such as proficiency with WhatsApp, Zoom, Microsoft OneNote, Microsoft PowerPoint, learning videos, and projectors. In contrast, regarding pedagogical and material abilities, the non-certified teachers have yet to be able to apply lesson plans to learning and continue to struggle to answer some predetermined questions.